ANALYSIS OF VALUE ADDED TAX POTENTIAL REVENUE USING INPUT-OUTPUT TABLE - Firdiyawan Lisdiyanto; Suparna Wijaya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Although the number of Value-Added-Tax (VAT) revenue almost increases every year, the government can still optimize VAT revenues. The research aims to calculate the possible VAT revenue by sector from 2016 until 2018. By knowing the possible VAT revenue, government can prioritize specific sector. The analysis used in this research is quantitative descriptive. The calculation of potential VAT revenue uses data from the Indonesian Input-Output Table. VAT revenue not collected due to specific regulations is calculated based on the tax expenditure report issued by the Ministry of Finance. The results showed that the VAT potential revenue always increased every year during the research year, namely Rp745 trillion in 2016, then rose to Rp799 trillion in 2017 and amounted to Rp859 trillion in 2018. During these three years, the potential for VAT revenue came from the manufacturing industry sector. The VAT coverage ratio grew positively during the year of research to 56.5% in 2016, rising to 58.1% in 2017 and 60.6% in 2018.